Essential perennials : the complete reference to 2700 perennials for the home garden - Clausen, Ruth Rogers, 1938-; Christopher, Thomas (Timber Press, 2014)
Essential Perennials helps you decide exactly which plants will bring you the beauty you want and will thrive in the conditions you can provide. Trusted garden experts Ruth Rogers Clausen and Thomas Christopher focus on what every gardener needs to know. For each plant you'll find flower color, season of bloom, foliage characteristics, height and width, light requirements, and hardiness and heat sensitivity. You'll also learn cultural tips, the most outstanding cultivars for each species, and whether a plant has any special requirements or potential problems.--COVER.